Strive to be First or Avoid Being Last: An Experiment on Relative Performance Incentives - E. Glenn Dutcher; Loukas Balafoutas; Florian Lindner; Dmitry Ryvkin; Matthias Sutter (Institute for the Study of Labor (IZA), 2015)
We utilize a laboratory experiment to compare effort provision under optimal tournament contracts with different distributions of prizes which motivate agents to compete to be first, avoid being last, or both. We find that the combined tournament contract incorporating both incentives at the top and at the bottom induces the highest effort, especially in larger groups. Avoiding being last produces the lowest variance of effort and is more effective at motivating employees compared to competing for the top.
Keywords: M52; J33; J24; D24; C90; 330; tournament; winner; loser; contract; experiment; learning